Optimasi Multirespon Purwarupa Electrical Discharge Machine (EDM) Menggunakan Metode Taguchi-Grey Relational Analysis - Angga Sateria; Eko Yudo; Zulfitriyanto Zulfitriyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2019)
EDM is one of the nonconventional machining processes when making workpieces with conventional machining processes is difficult. This process has been used effectively in machining hard, high-strength and high temperature materials such as high speed steel (HSS) materials. In this study, prototype of EDM machines was carried out with engine variables such as current (A), pulse on time (µs) and pulse off time (µs). The material used is high speed steel (HSS) material used in cutting tools such as turning tools and milling tools. Surface roughness and material removal rate are responses observed to determine the quality of material remaval. The quality characteristic of the surface roughness response is